Analysis of palm oil fuel ash, garnet waste and sawdust as modified asphalt binders and mixtures - Wan Noor Hin, Mior Sani; Putra Jaya, Ramadhansyah; Norhidayah, Abdul Hassan; Azman, Mohamed; As-Saffar, Zaid Hazim (Springer Nature, 2025)
Given the increasing traffic loads and challenging environmental conditions, significant attention must be devoted to modified asphalt binders using waste materials. Therefore, this study investigated the preliminary analysis of palm oil fuel ash (POFA), garnet waste and sawdust as modified asphalt binders and mixtures. The process involved thorough evaluations regarding several aspects: the chemical features of individual waste, the physical properties of individual modified asphalt binders of 0%, 3%, 6% and 9% by weight of asphalt and the mechanical characteristics of individual modified asphalt mixtures. Consequently, the topmost chemical composition is initiated in POFA is Si2O, garnet waste is Fe2O3, and sawdust consists CaO. The findings showed superior stability of POFA-modified asphalt mixture proceeded along with garnet waste-modified asphalt mixture and sawdust-modified asphalt mixture. Thus, this outcome indicates a practical evaluation of the three types of waste, demonstrating good bonding and contributing to improved performance when used as a combination in asphalt modification.